2014
DOI: 10.1155/2014/187019
|View full text |Cite
|
Sign up to set email alerts
|

AcetylcholinesteraseInhibition by Biofumigant (Coumaran) from Leaves ofLantana camarain Stored Grain and Household Insect Pests

Abstract: Recent studies proved that the biofumigants could be an alternative to chemical fumigants against stored grain insect pests. For this reason, it is necessary to understand the mode of action of biofumigants. In the present study the prospectus of utilising Lantana camara as a potent fumigant insecticide is being discussed. Inhibition of acetylcholinesterase (AChE) by Coumaran, an active ingredient extracted from the plant L. camara, was studied. The biofumigant was used as an enzyme inhibitor and acetylthiocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 30 publications
0
37
0
1
Order By: Relevance
“…Due to the important role of secondary metabolites, which play in insect-plant interaction that are often involved with plant defense, their bioactivities can be used against stored grain insect pests (Rajashekar et al, 2014). Thus, the presence of secondary metabolite classes may be a useful indicator for both efficacy and potential of phytochemical bioactivity (Gupta et al, 2013).…”
Section: Preliminary Qualitative Phytochemical Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the important role of secondary metabolites, which play in insect-plant interaction that are often involved with plant defense, their bioactivities can be used against stored grain insect pests (Rajashekar et al, 2014). Thus, the presence of secondary metabolite classes may be a useful indicator for both efficacy and potential of phytochemical bioactivity (Gupta et al, 2013).…”
Section: Preliminary Qualitative Phytochemical Screeningmentioning
confidence: 99%
“…According to their report, most abundant volatile organic components were (Z)-9,7-octadecadienal and palmitic acid comprising 25.47% and 14.97% of the total spectrums in A. indica seed and cake respectively. ,1,4,5,6,7,8,9,1,7.alpha.,9a.beta ,1,2,3,4,5,6,7,4,9,[1S(1.alpha.,4.alpha.,7.alpha Several reports have demonstrated that the plant volatiles produce insect mortality by inhibiting acetylcholinesterase enzyme and bio-fumigants could be neurotoxic based on behavioral symptoms similar to those produced by organophosphates (Rajashekar et al, 2014). In that account, the insecticidal and repellent nature of the leaf powders of A. indica manifested by adult insects of S. zeamais in both contact and vapor forms may be linked to the main volatile compounds extracted reportedly acting alone or in synergy with other minor constituents (Adjalian et al, 2015).…”
Section: Analysis Of the Volatile Organic Compoundsmentioning
confidence: 99%
“…exhibited insecticidal activity against S. zeamais and T. castaneum by enzymatical degradation of glucocapparin (Gueye et al 2011(Gueye et al , 2013. In recent work, Rajashekar et al (2014b) reported coumarin, a biofumigant isolated from L. camara as acetylcholine esterase inhibitor of S. oryzae.…”
Section: Mode Of Actionmentioning
confidence: 99%
“…L. camara has also been used in traditional herbal medicines for treating a variety of ailments, such as cancer, skin itches, leprosy, rabies, chicken pox, measles, asthma and ulcers [61]. Lantana camara has been tested as an alternative to fumigants in stored grains [62]. Therefore, there is a need of finding out more information about the toxicity of Lantana camara to the health of human being.…”
Section: Pentacyclic Triterpenoids From Lantana Camaramentioning
confidence: 99%